Photoluminescence in amorphous (PbLa)TiO3 thin films deposited on different substrates - Rangel, J. H.; Carreno, NLV; Leite, E. R.; Longo, Elson [UNESP]; Campos, CEM; Lanciotti, F.; Pizani, P. S.; Varela, José Arana [UNESP] (Elsevier B.V., 2002)
Pb1-XLaXTiO3 thin films, (X = 0.0; 13 and 0.27 mol%) were prepared by the polymeric precursor method. Thin films were deposited on Pt/Ti/SiO2/Si (1 1 1), Si (1 0 0) and glass substrates by spin coating, and annealed in the 200-300degreesC range in an O-2 atmosphere. X-ray diffraction, scanning electron microscopy and atomic force microscopy were used for the microstructural characterization of the thin films. Photoluminescence (PL) at room temperature has been observed in thin films of (PbLa)TiO3. The films deposited on Pt/Ti/SiO2/Si substrates present PL intensity greater than those deposited on glass and silicon substrates. The intensity of PL in these thin films was found to be dependent on the thermal treatment and lanthanum molar concentration. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: photoluminescence; thin films; (PbLa)TiO3